2023
DOI: 10.1177/14613484231152850
|View full text |Cite
|
Sign up to set email alerts
|

Influences of wheel polygon amplitude on wheel-rail vibration and sound radiation

Abstract: Wheel polygon amplitude can greatly affect wheel-rail vibration and sound radiation. Based on multi-body dynamics theory, a vehicle-track rigid-flexible coupling dynamics model was established. According to the actual running wear condition of the wheel, the wheel-rail vibration response was calculated and analyzed (the order of wheel polygons is 20, and the polygon amplitude is 0.01/0.02/0.03/0.04 mm, respectively). Together with the finite element/boundary model of the wheel, the calculated wheel-rail force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, during the actual operation of high-speed trains, the axle box bearings of high-speed trains are coupled with other components, which will be subject to various external excitations, among them, wheel-rail excitation is the main source of vibration acceleration experienced by various components of the train. Such as wheel polygon [28][29][30][31][32], wheel flat scar [33][34][35], track irregularity [2,33,36,41], etc. Based on the multi-body dynamics theory, the literature [29] established a rigid-flexible coupling dynamic model of vehicle-track, analyzed the influence of polygon amplitude on the time-frequency domain of wheel noise, and the research results showed that when the polygon order is 20, with the increase of polygon amplitude, the wheel-rail vertical force and the acceleration of wheel-rail and rail plate gradually increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during the actual operation of high-speed trains, the axle box bearings of high-speed trains are coupled with other components, which will be subject to various external excitations, among them, wheel-rail excitation is the main source of vibration acceleration experienced by various components of the train. Such as wheel polygon [28][29][30][31][32], wheel flat scar [33][34][35], track irregularity [2,33,36,41], etc. Based on the multi-body dynamics theory, the literature [29] established a rigid-flexible coupling dynamic model of vehicle-track, analyzed the influence of polygon amplitude on the time-frequency domain of wheel noise, and the research results showed that when the polygon order is 20, with the increase of polygon amplitude, the wheel-rail vertical force and the acceleration of wheel-rail and rail plate gradually increased.…”
Section: Introductionmentioning
confidence: 99%
“…Such as wheel polygon [28][29][30][31][32], wheel flat scar [33][34][35], track irregularity [2,33,36,41], etc. Based on the multi-body dynamics theory, the literature [29] established a rigid-flexible coupling dynamic model of vehicle-track, analyzed the influence of polygon amplitude on the time-frequency domain of wheel noise, and the research results showed that when the polygon order is 20, with the increase of polygon amplitude, the wheel-rail vertical force and the acceleration of wheel-rail and rail plate gradually increased. In literature [33], a three-dimensional coupled model of vehicle axle box bearings was built using UM and Simulink to simulate the dynamic characteristics of coupling between wheel flat scar and faulty bearings.…”
Section: Introductionmentioning
confidence: 99%